A qualitative study to explore the barriers and enablers for young people with disabilities to access sexual and reproductive health services in Senegal. Issue 50 (12th June 2017) - Burke, Eva; Kébé, Fatou; Flink, Ilse; van Reeuwijk, Miranda; le May, Alex
Abstract: Use of sexual and reproductive health (SRH) services is low amongst young people in Senegal. Although the evidence base on young people's SRH needs is growing, research on access to SRH services amongst young people with disabilities is negligible. Our study explored the SRH vulnerabilities and expressed needs for young people with disabilities, experiences of accessing SRH services and what access challenges they face. Male and female peer researchers conducted 17 focus group discussions and 50 interviews with young women and men with disabilities between 18 and 24 years with a physical, visual or hearing impairment in Dakar, Thies and Kaolack in Senegal. Young people with disabilities reported very low knowledge about, and use of, SRH services including contraception and gynaecological consultations, but demonstrated a need for them, and were reliant on others to accompany them to service providers, impeding their access to confidential services. Multiple cases of rape were revealed, particularly amongst women with hearing impairments. Key barriers to SRH services were financial barriers, provider attitudes and accessibility (related to their disability). SRH policies and interventions for young people with disabilities should be based on an understanding of the intersection of youth, disability and gender. Urgent and targeted action is needed to improve provider attitudes and capacity to respond to the needs of young people with disabilities and to address the burden of sexual violence.